WAKAF PRODUKTIF : UPAYA MEMAKSIMALKAN POTENSI WAKAF - Ma'mun, Mohamad Ma'mun (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2023)
Waqf is one of the teachings in Islam that is very urgent. Waqf has a strategic value in Islam. Waqif (people who donate waqf) will continue to receive rewards if the waqf assets continue to be used, even though the waqif has died. Besides having a vertical dimension (relationship with the Creator), waqf also has a horizontal dimension (relationship with fellow human beings). In Islam, there are several concepts of giving charity to help fellow human beings, including zakat, alms, infaq, and endowments. Waqf if managed professionally will bring in large income. Unfortunately, most waqf assets in Indonesia are still managed in a simple and traditional manner. Many waqf assets are used more unproductively. Use is limited to schools, places of worship, orphanages and so on. Such use is already useful, but it can be developed with maximum results. There needs to be a re-actualization in waqf management, waqf management which was previously still traditional, must be changed to professional management. One such method is productive waqf. Productive waqf is a new method of managing waqf so that waqf is more efficient and provides more value for the welfare of Muslims.